P116 Effects of macitentan on right ventricular remodeling in pulmonary arterial hypertension – results from the REPAIR study interim analysis. (12th November 2019) - Kiely, D; Rosenkranz, S; Galiè, N; Channick, R; Cottreel, E; Martin, N; Peacock, A; Tawakol, A; Torbicki, A; Vonk Noordegraaf, A
Abstract : Introduction and objectives: In pulmonary arterial hypertension (PAH) right ventricular (RV) function is impaired as reflected in a decrease in stroke volume. The REPAIR study aims to evaluate the effect of macitentan on RV structure and function in patients with PAH. Methods: REPAIR (NCT02310672 ) is a 52-week, open-label, multicenter study evaluating the effect of macitentan on right ventricular (RV) remodeling and function as determined by cardiac magnetic resonance imaging (MRI). Macitentan was initiated as monotherapy or in combination with a phosphodiesterase-type 5 inhibitor. The two primary endpoints were change from baseline at Week 26 in RV stroke volume (RVSV), determined by pulmonary artery flow MRI, and pulmonary vascular resistance (PVR), measured by right heart catheterization. A full evaluation of the RV was also performed using MRI. The results of the pre-specified efficacy interim analysis, performed in the first 42 evaluable patients, are presented. Results: In the interim analysis, at baseline, mean (SD) age was 46.3 (14.9) years, 31 patients were female, median (range) 6-minute walk distance was 376 (180–724) m and patients were WHO functional class II (n=19) or III (n=23). The RVSV was significantly increased and PVR was significantly decreased at Week 26 (Table). As both primary endpoints were met, enrollment in the study was ended. Conclusions: REPAIR is the first multicenter study in PAH using an MRI variable as a primary endpoint, and showed improvement in RV function with macitentan. These data also demonstrate that RVSV can be used as a primary endpoint to study treatment efficacy in PAH.